2007
DOI: 10.2193/2006-376
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seasonal Flooding on Seed Availability for Spring Migrating Waterfowl

Abstract: We hypothesized the seed biomass available to migrating waterfowl would be higher in spring‐ versus fall‐flooded wetlands. To test this hypothesis we conducted an experiment using 5 pairs of wetland impoundments in northern Missouri, USA (2000‐2002). We strategically assigned one impoundment of each pair to either a fall or spring treatment group. We estimated seed biomass in fall and in spring by clipping seed heads and collecting soil cores at 20 random locations within each impoundment. We placed exclosures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…Although many studies have reported depletion of local waterfowl food sources (e.g., Percival et al 1996, Amano et al 2006, Nolet et al 2006, Greer et al 2007, ours is the first to document depletion of a food in an area the size of the MAV. Regional depletion of an important food source is not unequivocal evidence that wintering waterfowl populations are limited by food availability, but it is consistent with the hypothesis.…”
Section: Discussionmentioning
confidence: 59%
“…Although many studies have reported depletion of local waterfowl food sources (e.g., Percival et al 1996, Amano et al 2006, Nolet et al 2006, Greer et al 2007, ours is the first to document depletion of a food in an area the size of the MAV. Regional depletion of an important food source is not unequivocal evidence that wintering waterfowl populations are limited by food availability, but it is consistent with the hypothesis.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, priorities for continental‐scale conservation planning should continue to recognize the importance of protecting, restoring, enhancing, and managing wetland habitats used by spring‐migrating ducks in large regional landscapes such as the UMRGLR. At more local scales we encourage wetland managers to consider waiting to flood some wetlands until late winter or early spring because this has been shown to increase seed biomass availability (Heitmeyer 2006, Greer et al 2007). Our estimates of plant, invertebrate, and total duck food biomass during spring migration should be used to refine wetland habitat objectives of the UMRGLR JV.…”
Section: Management Implicationsmentioning
confidence: 99%
“…We washed samples with water over a graduated series of 2-3 sieves (mesh sizes 18 [1.00 mm], 35 [500 mm], and 60 [250 mm]) depending on the quantity of vegetation present (Penny 2003;Reinecke and Hartke 2005;Greer et al 2007). We separated seed heads and seeds from plant debris and dried for 24 h at 87uC (Manley et al 2004;Stafford et al 2006a (Greer et al 2007). We classified seeds as large if they were retained by the #35 sieve (e.g., largeseed smartweed Polygonum pensylvanicum, millets Echinochloa spp., and beggarticks Bidens spp.)…”
Section: Estimating Moist-soil Plant Seed Abundancementioning
confidence: 99%